Przegląd reakcji chloraminy-T i dichloraminy-T z kationami metali w celu określenia możliwości wykorzystania ich wielkocząsteczkowych analogów w oczyszczaniu wód - Kociołek-Balawejder, Elżbieta; Ciechanowska, Agnieszka; Stanisławska, Ewa (A Review of Chloramine-T and Dichloramine-T Reactions with Metal Cations to Determine the Possibility of Their Macromolecular Analogues Application in Water Purification, 2008)
Reactions of chloramine-T and dichloramine-T with metal cations (for example Hg(I), Tl(I), Ag(I), Fe(II), Cr(II), Sn(II), Hg(II), Fe(III), Al(III), Cr(III), As(III) Sb(III), Ti(III, Th(IV), Zr(IV)) were used in redox titration and organic synthesis. According to that fact we investigate such reactions using high molecular weight analogues of chloramine-T and dichloramine-T as heterogeneous oxidants containing active chlorine. The deironing of water is one of the most important processes where such water-insoluble oxidants can be applied. The study also found that in the course of these reactions it is possible to obtain specific polymer materials, which include dispersed iron oxide nanoparticles in their internal structure. These materials (hybrid polymers) can be used as specific adsorbents and catalysts. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 183-191